2014
DOI: 10.3386/w20153
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Ideology: Experimental Evidence on Anti-Americanism in Pakistan

Abstract: and the Yale Conference on Political Economy and Development for helpful comments and suggestions. Sarah Brierley provided excellent research assistance. We also thank the Center for Global Management at UCLA Anderson for financial support. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 27 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…For this reason, some research has provided respondents with the information that the researcher will be made aware of their actions as a ways of manipulating extrinsic motivations stemming from possible social sanctions. In so doing, these studies have found such treatment to significantly alter behavior, making respondents more likely to act in norm-compliant ways (Bursztyn, Egorov, and Fiorin 2017;Bursztyn et al Forthcoming).…”
Section: Empirical Strategymentioning
confidence: 99%
“…For this reason, some research has provided respondents with the information that the researcher will be made aware of their actions as a ways of manipulating extrinsic motivations stemming from possible social sanctions. In so doing, these studies have found such treatment to significantly alter behavior, making respondents more likely to act in norm-compliant ways (Bursztyn, Egorov, and Fiorin 2017;Bursztyn et al Forthcoming).…”
Section: Empirical Strategymentioning
confidence: 99%
“…The paper is also related to the literature that has studied the determinants and implications of anti-Americanism or anti-Western values. See for instance Gentzkow and Shapiro (2004), Beath, Christia and Enikolopov (2017), Cantoni et al (2016, and Bursztyn et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Section 5 concludes. 6 Our paper also relates to a literature on identity in economics (Akerlof and Kranton, 2000;Akerlof, 2016;Akerlof and Rayo, 2020;Atkin et al, 2020;Bursztyn et al, 2020;Chen and Li, 2009;Cohn et al, 2015;Enke et al, 2019a;Jia and Persson, 2019;Lowes et al, 2015;Oh, 2019).…”
Section: Introductionmentioning
confidence: 86%